PERSEPSI ANAK SEKOLAH DASAR TENTANG PERILAKU MEROKOK PADA SISWA SD NEGERI GROGOL 05 KOTA JAKARTA BARAT - Nurapipah; Nurul Febrianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted with the aim of knowing the perceptions of elementary school children on smoking behavior in Grogol 05 State Elementary School students in West Jakarta in grades 5 A and B with a total of 52 students. This research is a descriptive quantitative study using a frequency distribution method. Data collection techniques in the form of closed questionnaires or questionnaires. The results of the study found that the majority of Grogol 05 Elementary School children's perceptions were "negative" towards smoking behavior with 22 (73.1%) students who answered and knowledge of detailed information on the dangers of smoking, there were 27 (84.6%) with students having "Less" knowledge. Unfavorable findings in the elementary school environment, even though children have negative perceptions of smoking behavior, children have very little knowledge of more detailed information about the substances contained in cigarettes and the dangers arising from smoking behavior.